The Impact of Non-Performing Loan, Loan to Deposit Ratio, Operating Expenses to Operating Income, and Net Interest Margin on Banking Stock Prices - Reza Pahlevi Ramadhan; Maiyaliza (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The purpose of this study is to examine the impact of non-performing loans, loan-to-deposit ratio, operating cost-to-operating income, and net interest margin on the share prices of traditional financial institutions listed on the Indonesia Stock Exchange during the period 2020–2024. A quantitative methodology was used, drawing on secondary data from the market capitalization-based financial statements of the top ten banks. The sample was selected through purposive sampling, and the data were analyzed using multiple linear regression. The results show that, simultaneously, non-performing loans, loan-to-deposit ratio, operating cost-to-operating income, and net interest margin have a statistically significant influence on banking stock prices. However, when assessed individually, only the BOPO variable exhibits a significant and negative effect. This indicates that higher operational inefficiency tends to reduce investor interest and negatively impact stock valuation in the banking sector. In contrast, the NPL, LDR, and NIM variables, although aligned with theoretical expectations, did not demonstrate statistically significant effects within the model. The coefficient of determination (R²) is 0.240, meaning that approximately 24% of the variation in stock prices can be explained by the four independent variables, while the remaining 76% may be attributed to other external or internal factors not captured in the model. These findings underscore the critical role of operational efficiency as reflected by the BOPO ratio, particularly during periods of economic uncertainty such as the post-pandemic era. The study offers useful insights for investors, banking management, and policymakers in making strategic financial decisions based on fundamental performance indicators.